Complete mitochondrial genomes of two water mite species: Hygrobates (H.) longiporus and Hygrobates (rivobates) taniguchii (Acari, Trombidiformes, Hygrobatoidea). Issue 3 (2nd July 2020) - Hiruta, Shimpei F.; Morimoto, Shizuko; Yoshinari, Gyo; Goldschmidt, Tom; Nishikawa, Kanto; Shimano, Satoshi
Abstract: We determined the complete mitochondrial genome sequences of two water mites, Hygrobates ( Hygrobates ) longiporus and H. ( Rivobates ) taniguchii . The length of the entire mitogenome of these two species is 13, 721 bp and 13, 770 bp long, respectively. Both of them contain 13 proteins, two rRNAs, and 22 tRNAs for a total of 37 gene products. The gene order of Hygrobates is almost identical to the two species of Unionicola we included in the analysis, with some difference in the position of transfer RNA genes. Phylogenetic analyses highly support these Hygrobates species form a clade with other species of the Hygrobatoidea.